Gut Microbiota Diversity Between Normal And Moribund Orange-Spotted Grouper Epinephelus coioides in the Merbok River Using 16S rRNA Gene Amplicon Sequencing - Lau, Cher Chien; Mohd Nor, Siti Azizah; Mohd Noor, Mohd Ezhar; Afiqah-Aleng, Nor; Tan, Min Pau; Ng, Su Khi; Yik Sung, Yeong; Munir, Mohammad Bodrul; Danish-Daniel, Muhd (Malaysian Applied Biology, 2025)
This study was conducted in the Merbok River, northwest Peninsular Malaysia, which is exposed to annual episodes of pollution. The microbiota of foregut, midgut and hindgut were analyzed to identify differences in the gut microbiome between three normal and two moribund orange-spotted grouper, Epinephelus coioides. Live specimens were collected two weeks after an episode of mass mortality. The 16S amplicon sequencing targeting the V3-V4 highly variable region revealed similar community richness among samples with common dominant phyla, including Proteobacteria, Actinobacteria, Tenericutes, Cyanobacteria and Acidobacteria. Significantly higher abundance of phylum Cyanobacteria, genus Sphingomonas and species Eubacterium coprostanoligenes in normal guts was likely beneficial in maintaining gut health. Moribund guts were enriched with opportunistic pathogens, including Escherichia-Shigella, Clostridium sensu stricto 1 and Shewanella. In particular, moribund hindguts displayed a reduced Firmicutes-to-Proteobacteria ratio and significant enrichment of Photobacterium damselae subsp. damselae, indicating dysbiosis and predicted to associate with skin conditions. Higher abundance of Photobacterim in moribund fish hindguts may also correlate with the increased chitinolytic activity and altered metabolic pathways. The outcomes of the study provide fundamental insights into the roles of gut microbiota in regulating the orange-spotted grouper's survival in a polluted environment.